THE ROLE OF COMMUNICATION IN THE EDUCATION OF INDIVIDUAL CHARACTER AND ITS PRACTICAL IMPORTANCE. - Toshpulatov Ibrohim Ikromjonovich; Ikromjоnova Zilola Ibrahim qizi; Ikromjonova Diyora Ibroxim qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the authors analyzes the role of communication and its practical significance in cultivating individual traits that are important in the educational process today. He also stressed that in order to effectively organize pedagogical communication, teachers must have sufficient knowledge, skills and competencies in pedagogy, psychology, pedagogical skills and pedagogical technologies. Throughout the article, the author discusses both types of interactions in the communication process.